ON THE IMPORTANCE OF EUGEN EHRLICH'S THEORY OF LAW FOR CONSTITUTIONAL LAW - MALISKA, MARCOS (Ehrlich's Journal, 2023)
The Ehrlichian concepts of "living law" and "association" can help constitutional law in the investigation of the relationship between constitution and pluralism. When Ehrlich describes the forces of society, which produce through their various associations a living law, he shows constitutional law the importance of law existing outside the State Law. The Constitution does not only regulate the State, but it also contains norms for society. Fundamental rights are binding standards for both the state and civil society. Thus, the current concept of Constitution makes the validity of law no longer in State law, but in the Constitution. In this way, the existence of a living law produced by the social associations finds its validity in the Constitution. The relation between constitutional law and sociology of law has in Ehrlich's work one of the most significant elements of connection. The opening of the Constitution to pluralism is not only a process that begins and ends in the interpretation of the constitutional text. Openness to pluralism implies the recognition of a law that exists in practice and moves society. Constitutional interpretation must be attentive to this law. The constitutional validity of the law brings the necessary limits that a sociological analysis of law often fails to observe. The pluralistic societies of the 21st century recognize the insufficiency of the legislated law as the sole and exclusive form of social regulation. New legal forms emerge and need to be contemplated by a theory of law open to the pluralism of legal sources.